VERIFICAÇÃO AUTOMÁTICA DAS MEDIDAS DE SEGURANÇA CONTRA INCÊNDIO DO ESTADO DE SÃO PAULO NO PROJETO DE HABITAÇÃO MULTIFAMILIAR - Kater, Marcel; Ruschel, Regina (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The automation of the process of verifying building codes is crucial for the Construction Industry. One way to obtain this solution is by automated rule checking. This research evaluated the feasibility of automatic verification of fire safety requirements in the design of buildings with BIM. We implemented an automatic check, for the fire regulations of the state of São Paulo, in buildings of multifamily private residential use. At first, we identified the relevance and understood the problem in practice. We performed a bibliographic review of the main issues involved as well as a survey among the agents involved in the verification of fire design standards. Then a solution was proposed and developed in BIM with the SOLIBRI software. This development is the emphasis of this article. The solution comprehends a set of rules, composing an automatic rules verification system for fire safety standards, along with the modeling guidelines required to execute these rules. Finally, the system was evaluated by verifying its compliance with the structured rule-checking process outlined by Eastman et al. (2009). The implemented automatic verification rules represent 9% of the requirements related to technical instructions and standards involved in fire regulations of the state of São Paulo for multifamily residential buildings. However, analyzing the similarity of the measures implemented against the others, it turns out that the adopted strategy could be used in almost all the remaining universe. Therefore, the solution demonstrates the potential of making the application of federal, state, municipal fire regulations effective and efficient.